Histopathologic observations in a coccidiosis model of Eimeria tenella - Zhixin Sun; Linlin Chen; Mengyu Lai; Xixi Zhang; Jie Li; Zhiping Li; Dongming Yang; Mengyang Zhao; Dongdong Wang; Pei Wen; Fengting Gou; Yuexin Dai; et al. (Animal Models and Experimental Medicine)
Abstract Background Species of the genus Eimeria cause coccidiosis in chickens, resulting in a huge burden to the poultry industry worldwide. Eimeria tenella is one of the most prevalent chicken coccidia in China, and E. tenella infection causes hemorrhagic cecitis. Methods Using an established model of coccidiosis in chickens combined with necropsy, imaging of pathological tissue sections, and other techniques, we evaluated the gross and microscopic lesions of cecal tissue within 15 days after inoculation with sporulated oocysts and described the endogenetic developmental process and relationship between E. tenella infection and enteritis development in chickens. Results We observed three generations of merogony and gamogony in E. tenella. We observed gross lesions in the cecum from 84 hpi (hours post inoculation) and microscopic lesions from 60 hpi. The lesions in the cecum mainly exhibited hemorrhagic enteritis. Their severity increased with the onset of the second generation of merogony. The lesions began to alleviate by the end of the endogenous stages of E. tenella. Conclusion We show, for the first time, the complete observation of a series of changes in enteritis caused by 5 × 103 E. tenella oocysts. This study provides reference materials for E. tenella research and pathological diagnosis.